From the use of exposure index in quality control testing to the use of exposure index for quality control of clinical images - Ioannis A. Tsalafoutas (14776939) (2022)
Aim The exposure index (EI) is used in routine quality control (QC) tests performed in the radiographic equipment installed in our hospitals. This study aimed at investigating the factors affecting the calculation of EI in QC and clinical images, and the implementation of target EI (EIT) and deviation index (DI) in clinical practice. Methods The EI is 100 times the incident air kerma (IAK) in μGy on the image receptor, using the RQA-5 X-ray beam quality. Conformance to this relationship was investigated in QC images and clinical images acquired using anthropomorphic phantom body parts and different examination protocols, tube potential settings and radiation field sizes. Furthermore, a survey on EIT and DI data from clinical images was performed. Results Though automatic exposure control (AEC) systems have been adjusted for an IAK of 2.5 μGy, for most anthropomorphic phantom images the EIs were far from 250, depending on the manufacturer, the anatomy imaged, and the examination protocol. Regarding the survey results, DI calculation was feasible in only 38 % of the systems, since for the rest EIT values have not been set. However, the rationale based on which EIT have been selected is unclear. Some systems use only one while others many different EIT values. Conclusion Before using EI for quality control of clinical images image all receptors and AEC systems should be properly calibrated. Then, the methodology of selecting appropriate EIT should be refined, since the EI calculation may vary, depending on the manufacturer, the anatomy imaged, and the examination protocol. Other Information Published in: European Journal of Radiology Open License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ejro.2022.100454